Clinical features and outcomes of Sweet's syndrome associated with non‐tuberculous mycobacterial infection and other associated diseases. Issue 5 (13th October 2015) - Chaowattanapanit, Suteeraporn; Choonhakarn, Charoen; Chetchotisakd, Ploenchan; Sawanyawisuth, Kittisak; Julanon, Narachai
Abstract: Sweet's syndrome (SS) is associated with various diseases including non‐tuberculous mycobacterial infection (NTM). Recent reports have shown that SS associated with NTM is increasing. Clinical features of SS associated with NTM may be different from SS associated with other associated diseases. The aim of the present study was to compare clinical parameters and treatment outcomes of SS associated with NTM and other associated diseases. Patients from January 2004 to April 2014 diagnosed with SS were retrospectively enrolled. Clinical variables were compared between SS patients with and without NTM infection. There were 51 SS patients during the study period; 36 patients (70.59%) had NTM. Clinical variables between the NTM and other associated diseases were comparable: age, sex, and pattern and locations of skin lesions. Five laboratory factors were significantly different between the groups including white blood cell counts (NTM 25 800 vs 12 850 cells/mm 3 ), lymphocyte percentages (13.0% vs 18.7%), monocytes (3.0% vs 7.2%), blood urea nitrogen (BUN) (11.7 vs 8.1 mg/dL) and serum creatinine (Cr) (1.0 vs 0.7 mg/dL). The presence of markedly high white blood cell counts, a low percentage of mononuclear cells and high BUN/Cr levels in SS may be a clinical clue to recognize the association with NTM infections; particularly in dissemination.